A Perspective on the Interplay of Ultraviolet-Radiation, Skin Microbiome and Skin Resident Memory TCRαβ+ Cells - Patra, VijayKumar; Laoubi, Léo; Nicolas, Jean-François; Vocanson, Marc; Wolf, Peter (Frontiers in Medicine, 2018)
The human skin is known to be inhabited by diverse microbes, including bacteria, fungi, viruses, archaea, and mites. This microbiota exerts a protective role against infections by promoting immune development and inhibiting pathogenic microbes to colonize skin. One of the factors having an intense effect on the skin and its resident microbes is ultraviolet-radiation (UV-R). UV-R can promote or inhibit the growth of microbes on the skin and modulate the immune system which can be either favorable or harmful. Among potential UV-R targets, skin resident memory T cells (TRM) stand as well positioned immune cells at the forefront within the skin. Both CD4+ or CD8+ αβ TRM cells residing permanently in peripheral tissues have been shown to play prominent roles in providing accelerated and long-lived specific immunity, tissue homeostasis, wound repair. Nevertheless, their response upon UV-R exposure or signals from microbiome are poorly understood compared to resident TCRγδ cells. Skin TRM survive for long periods of time and are exposed to innumerable antigens during lifetime. The interplay of TRM with skin residing microbes may be crucial in pathophysiology of various diseases including psoriasis, atopic dermatitis and polymorphic light eruption. In this article, we share our perspective about how UV-R may directly shape the persistence, phenotype, specificity, and function of skin TRM; and moreover, weather UV-R alters barrier function, leading to microbial-specific skin TRM, disrupting the healthy balance between skin microbiome and skin immune cells, and resulting in chronic inflammation and diseased skin.